(untitled) (Journal of Informatics Education and Research, 2026)
This study seeks to examine the role played by Facebook in shaping and reinforcing feelings of hostility and affiliation toward Islamic intellectual currents, with particular focus on the Salafi current. The prominence of this current within Algerian society has been driven by a set of social, political, and cultural factors. To achieve the objectives of the study, the researchers adopted a descriptive survey methodology, relying on a questionnaire as the primary data collection tool. The electronic questionnaire was distributed to a convenience sample consisting of 150 male and female Facebook users. The findings of the study reveal that Facebook has played a significant role in strengthening feelings of affiliation while simultaneously intensifying feelings of hostility toward the Salafi intellectual current in Algeria. This is largely attributed to the absence of genuine and institutionalized media platforms dedicated to religious discourse. As a result, proponents of Salafi thought and their followers have increasingly turned to virtual platforms to disseminate and defend their ideological orientation. This trend, however, has been met with strong opposition from various actors particularly secular groups who reject Salafi projects on the grounds that they represent a Wahhabi, takfiri, and extremist ideology.